2023
DOI: 10.1021/acsanm.3c00144
|View full text |Cite
|
Sign up to set email alerts
|

Development of Perovskite Quantum Dots for Two-Dimensional Temperature Sensors

Abstract: In situ temperature measurement for closed systems is always challenging due to various physical limitations. With the aim to visualize the heat transfer phenomena in situ continuously with a longer time scale, octylamine substituted CsPbBr3 perovskite quantum dots (QDs) are synthesized, leading to its thermo-sensitity being doubled. An optical-based 2D temperature sensor based on these ligand-modified QDs is developed, targeting microreactors and other circumstances where conventional thermal sensing protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Brites et al 230 also used Eu 3+ /Tb 3+ codoped nanoparticles suspended in water to measure the temperature gradient imposed along a capillary tube with ∼65 μm spatial resolution (Figure 8b). Zhu et al 231 recently demonstrated 2D thermometry in microchannels using the temperature-dependent PL intensity of octylamine substituted CsPbBr 3 perovskite QDs, including transient measurements of laminar water flow, with ∼10 μm spatial resolution and 200 ms temporal resolution. As a potential strategy for thermometry in microfluidic devices that would not require dispersing luminescent nanomaterials in the fluid, Savchuk et al 232 developed PDMS/NaYF 4 :Yb 3+ ,Er 3+ composites suitable for ratiometric thermometry that also maintain the transparency of PDMS.…”
Section: Microfluidics and Nanofluidsmentioning
confidence: 99%
“…Brites et al 230 also used Eu 3+ /Tb 3+ codoped nanoparticles suspended in water to measure the temperature gradient imposed along a capillary tube with ∼65 μm spatial resolution (Figure 8b). Zhu et al 231 recently demonstrated 2D thermometry in microchannels using the temperature-dependent PL intensity of octylamine substituted CsPbBr 3 perovskite QDs, including transient measurements of laminar water flow, with ∼10 μm spatial resolution and 200 ms temporal resolution. As a potential strategy for thermometry in microfluidic devices that would not require dispersing luminescent nanomaterials in the fluid, Savchuk et al 232 developed PDMS/NaYF 4 :Yb 3+ ,Er 3+ composites suitable for ratiometric thermometry that also maintain the transparency of PDMS.…”
Section: Microfluidics and Nanofluidsmentioning
confidence: 99%